PENINGKATAN KEPATUHAN BADAN PUBLIK DALAM PELAKSANAAN UNDANG-UNDANG KETERBUKAAN INFORMASI PUBLIK DI KABUPATEN ACEH BARAT - Afrizal Tjoetra (Prodi Sosiologi FISIP Universitas Teuku Umar, 2017)
Government of Aceh and its regencies show commitment to public information transparency. Nevertheless, the implementation of UU KIP is still not maximized as applicable regulations. This is shown by a number of public information dispute submitted to the Commission on Information Aceh (Komisi Informasi Aceh–KIA) related information which is the obligation of Public Institutions..This research was conducted through a quantitative approach, with the survey method. The aims of research are to determine the readiness of the Public Institutions of West Aceh in implementing the constituent on Public Information, to investigate the Public Information Service in West Aceh Government in providing and announcing regular information and information immediately via the website / bulletin board at the Public Institutions, to know and see the direct efforts of the Public Institutions of West Aceh in preparing and providing the information available at any time to the applicant information, and to submit the feedback to the Public Institutions of West Aceh based on the results of research, so the strengthening of the main PPID and maid PPID in West Aceh. This research was conducted in three stages, namely through independent review, examination of the website and visits to the elected Public Institutions. Keywords: Public Information Transparency, Public Institutions, Public Information.